The morphology of paca (Cuniculus paca) testis with high dose of letrozole an aromatase inhibitor - Simões, Luciana Senna; Sasahara, Taís Harumi de Castro; Favaron, Phelipe Oliveira; Leal, Leonardo Martins; de Oliveira, Fabrício Singaretti [UNESP]; Fratini, Paula; Berger, Trish; Machado, Marcia Rita Fernandes [UNESP]; Miglino, Maria Angélica (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2020)
SUMMARY: The study reported the influence of the high and acute dose of Letrozole on the testis morphology in paca (Cuniculus paca), an aromatase inhibitor that reduces the endogenous estrogen, the essential hormone for spermatogenesis. Morphological changes were observed in seminiferous epithelium with germ cells with apoptotic characteristics and presence of vacuoles and nuclei in pycnose.
La morfología del testículo de paca (Cuniculus paca) con altas dosis de letrozol, un inhibidor de la aromatasa
Keywords: Gonadal; Spermatogenesis; Toxic